Domestic cooking practices influence the carotenoid and tocopherol content in colored cauliflower - Diamante, Marla Silvia [UNESP]; Borges, Cristine Vanz [UNESP]; Minatel, Igor Otavio [UNESP]; Jacomino, Angelo Pedro; Pereira Basilio, Leticia Silva [UNESP]; Monteiro, Gean Charles [UNESP]; Corrêa, Camila Renata [UNESP]; Oliveira, Rogerio Antonio de [UNESP]; Pereira Lima, Giuseppina Pace [UNESP] (Elsevier B.V., 2021)
Cauliflowers are generally associated with healthy diets due to their positive impact on health. This research aims to evaluate the effects of cooking processes (boiling, steaming and microwaving) and different preparation times, on the content of carotenoids and provitamin A and tocopherols, in cauliflowers and to verify the effect of the cooking process on maintaining the coloring. The results revealed that the thermal process influenced the antioxidant compounds release independent of genotype. The highest content of zeaxanthin and lutein was found in 'Verde di Macerata' after boiling for 20 min. 'Cheddar' presented the highest content of all carotenoids and when steamed for 20 min, the highest levels of provitamin A were observed. Microwaved and bolied 'Grafitti' for longer times showed the highest retention of tocopherol. The cooking did not negatively affect the visual aspect. 'Verde di Macerata' and 'Cheddar' may be good sources of carotenoids and tocopherols.
Keywords: Brassica oleracea var. botrytis; Provitamins A; Antioxidant compounds; CIELab